3D printed PCU/UHMWPE polymeric blend for artificial knee meniscus. (June 2018) - Araujo Borges, Raissa; Choudhury, Dipankar; Zou, Min
Abstract: 3D printing was used to fabricate porous polycarbonate-urethane (PCU) and ultra-high-molecular-weight polyethylene (UHMWPE) blend for the artificial meniscus to enable native lubrication mechanisms of the knee. 3D printed PCU and molded PCU and UHMWPE were used for comparison. Cross-sectional images of 3D printed PCU and PCU/UHMWPE blend showed 6.34% and 13.61% porosity, respectively, while no porosity was observed in molded samples. This porosity leads to 46% more fluid absorbed by 3D printed PCU than molded PCU. Rotational oscillating tests under conditions replicating the knee motion show 3D printed PCU has 27% less wear depth than molded PCU due to retained fluid in its porosity. Thus, 3D printing provides a facile approach to fabricate porous, customizable PCU implants that mimic meniscus lubrication. Graphical abstract: Image 1 Highlights: 3D printed PCU and PCU/UHMWPE blend were explored for artificial meniscus. 3D printing was used to provide porosity and enable natural lubrication of the knee. 3D printed PCU results in 27% wear depth reduction compared to molded PCU. SEM images show porosity in 3D printed samples and none in molded ones. 46% more fluid was absorbed by 3D printed PCU compared to molded PCU.